The RBT ethics code : mastering the BACB ethical requirements for registered behavior technicians - Bailey, Jon S.; Burch, Mary R. (New York, NY : Routledge, 2020)
"This practical textbook will enable students training to become registered behavior technicians (RBTs) to fully understand and follow the new RBT Ethics Code administered by the Behavior Analyst Certification Board (BACB). Starting with an overview of the role of ethics and core ethical principles, subsequent chapters provide concrete guidance for each of the three sections of the RBT Ethics Code: responsible conduct, responsibility to clients, and competence and service delivery. The authors then show correct and incorrect applications of each code item and provide practical examples and solutions for applying each section to everyday practice. Also included are test questions where RBTs can test themselves on their newfound knowledge along with a glossary, the complete RBT Code of Ethics, and suggested readings. This book is intended to serve as a primary text for the training of Registered Behavior Technicians (RBTs) as well as a reference and study guide for these RBTs as well as their trainers"--
How We Got Here -- Core Ethical Principles -- A Virtual Bill of Rights for RBTs -- Responsible Conduct -- Responsibility to Clients -- Competence and Service Delivery -- RBT Responsibilities to the Board.
OCLC-licensed vendor bibliographic record.
Keywords: Behavior Analyst Certification Board; Medical ethics; Behavior therapists; Behaviorism (Psychology); PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Cognitive Psychology; PSYCHOLOGY / Mental Health